2021
DOI: 10.3390/microorganisms9102023
|View full text |Cite
|
Sign up to set email alerts
|

Danofloxacin Treatment Alters the Diversity and Resistome Profile of Gut Microbiota in Calves

Abstract: Fluoroquinolones, such as danofloxacin, are used to control bovine respiratory disease complex in beef cattle; however, little is known about their effects on gut microbiota and resistome. The objectives were to evaluate the effect of subcutaneously administered danofloxacin on gut microbiota and resistome, and the composition of Campylobacter in calves. Twenty calves were injected with a single dose of danofloxacin, and ten calves were kept as a control. The effects of danofloxacin on microbiota and the resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 74 publications
(114 reference statements)
1
13
0
Order By: Relevance
“…We observed that the microbiome diversity of treated cattle was significantly disturbed in the short term, increasing ARGs conferring resistance to tetracyclines compared to control animals without exposure to OTC. This finding is consistent with previous studies that reported the perturbation of the gut microbiome following antibiotic treatment within a few days after antibiotic exposure [ 25 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…We observed that the microbiome diversity of treated cattle was significantly disturbed in the short term, increasing ARGs conferring resistance to tetracyclines compared to control animals without exposure to OTC. This finding is consistent with previous studies that reported the perturbation of the gut microbiome following antibiotic treatment within a few days after antibiotic exposure [ 25 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Subcutaneously administered enrofloxacin to calves achieved the intestinal concentration that could decrease intestinal bacteria 42 . Further, our metagenomic studies 21 , 22 have revealed that the fecal microbial diversity has been significantly changed in calves; some bacterial taxa responded differently to the low and high enrofloxacin doses. The fecal resistome profiles have been affected remarkably in FQs administered groups compared to the control groups 21 , 22 .…”
Section: Discussionmentioning
confidence: 84%
“…On the eighth day, both groups were administered a single dose of danofloxacin (8 mg/kg body weight, ADVOCIN™, danofloxacin mesylate , Pfizer Animal Health) in the neck, subcutaneously. The animal study was described in more detail in our recent publication 21 .…”
Section: Methodsmentioning
confidence: 99%
“…Both experimental and observational studies indicated that antibiotic use and thus, the resultant selection pressure is an important factor driving the emergence and persistence of ARB and their resistance genes [ 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 ]. Mastitis is the most frequent disease of dairy cattle; and ceftiofur is the most commonly used antimicrobial drug used to manage it [ 5 , 68 ].…”
Section: Use Of Beta-lactam Antibiotics In the Usa Dairy Cattle Farmsmentioning
confidence: 99%